Language Acquisition: Exploring Parental Strategies and Children's Linguistic Development - Pratiwi, Widya Rizky (Universitas Negeri Medan, 2024)
This study explores the language learning dynamics within a bilingual family in Malaysia, focusing on parental strategies and their influence on language acquisition in Bahasa and Malay. Employing a qualitative case study design, participants were purposively sampled from the researcher's friend's family. Meticulous observation activities assessed various aspects of the family's language environment, including parental language use, exposure to authentic materials, and correcting linguistic errors. Creswell's framework guided data analysis, thoroughly examining observational data to derive meaningful insights. Trustworthiness was established through prolonged engagement, triangulation, member checking, and peer debriefing. The findings revealed proactive parental approaches, such as creating daily communication contexts, utilizing diverse activities, and providing corrective feedback, which fostered a supportive language learning environment for the children. Overall, these efforts facilitated bilingualism and language proficiency in both Bahasa and Malay, highlighting the pivotal role of parental involvement. This study contributes empirical evidence of effective parental strategies in bilingual language development, enriching our understanding of SLA theories and bilingual language acquisition within familial contexts.